Chemical and Physical Characteristics of Four Strawberry Cultivar - Ozkaya, Okan; Dundar, Omur (Asian Journal of Chemistry, 2010)
Fruit pomological characteristics of different strawberry varieties grown in Adana province, Mediterranean region of Turkey were evaluated in this study. Camarosa, sweet charlie, california giant 4 and carmine cultivars were characterized. The varieties were compared for berry weight, total soluble solids, fruit acidity, total soluble solids/fruit acidity, pH, vitamin C, colour, individual sugars. The highest fruit weight average was obtained from camarosa and california giant 4 whereas they had the lowest total soluble solids. Vitamin C amount was higher in camarosa, sweet charlie and california giant 4 than carmine. Individual sugar contents of 4 varieties were very similar. All strawberry varieties that were analyzed for chemical and physical fruit characteristics had satisfactory results. Therefore, these cultivars can be grown in Adana province commercially.